Novel Pt (II) Complexes With Anticancer Activity Against Pancreatic Ductal Adenocarcinoma Cells - Erika Stefàno; Gianluca Rovito; Luca G. Cossa; Federica De Castro; Viviana Vergaro; Asjad Ali; Giulia My; Danilo Migoni; Antonella Muscella; Santo Marsigliante; Michele Benedetti; Francesco Paolo Fanizzi (Bioinorganic Chemistry and Applications)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive type of solid tumor that is becoming more common. cis-[PtCl2 (NH3)2] (in short cisplatin or CDDP) has been shown to be effective in treating various cancers, including PDAC. However, the development of resistance to chemotherapy drugs has created a need for the synthesis of new anticancer agents. Platinum-based drugs containing the bidentate ligand phenanthroline have been found to have strong antitumor activity due to their ability to cause DNA damage. In this study, we examined the ability of two Pt (II) cationic complexes, [Pt(η1-C2H4OR) (DMSO) (phen)]+ (in short Pt-EtORSOphen; R = Me, 1; Et, 2), to inhibit the growth and spread of BxPC-3 PDAC cells, in comparison to CDDP. The length of the alkyl chain and its associated lipophilic properties did not affect the anticancer effects of complexes 1 and 2 in BxPC-3 cells. However, it did appear to influence the rapid loss of mitochondrial membrane potential (ΔΨM), suggesting that these complexes could potentially be used as mitochondria-targeted lipophilic cations in anticancer therapy.